CASPT2 Study on the Low-Lying Electronic States of $m$-$C_6H_4F^+_2$ Ion (Journal of Atomic and Molecular Sciences, 2014)
Electronic states of the $m$-$C_6H_4F^+_2$ ion were studied by using the CASPT2and CASSCF methods in conjunction with a contracted atomic natural orbital (ANOL)basis set. For the five lowest-lying states, geometries and adiabatic excitation energies $(T_0)$ were calculated at the CASPT2 level. The CASPT2 $T_0$ values and CASPT2 $T'_v$ values are in reasonable agreement with the available experimental data. The assignmentsof the $B,$ $C,$ and $D$ states of the $m$-$C_6H_4F^+_2$ ion were difficult since the threestates are closely lying. Based on the CASPT2 $T_0$ calculations, the $X,$ $A,$ $B,$ $C,$ and $D$ states of the $m$-$C_6H_4F^+_2$ ion were assigned to $1^2A_2,$ $1^2B_1,$ $2^2B_1,$ $1^2A_1,$ and $1^2B_2,$ respectively,which supports the suggested assignment of the lowest excited state to $^2B_1$ byTsuchiya et al. based on their experiments.